Singing as a Strategy to Enhance the Ability to Speak for Early Childhood - Kristyana, Lidya Ndaru; Suharto, S. (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2014)
Song is one form of typical communication. Therefore, singing is implemented in this study as a strategy to enhance the ability to speak. This study is aimed to find out the role of songs in enhancing the ability to speak for children in early childhood. This classroom action research is conducted in two cycles, there are: planning, acting out and observing, as well as reflecting. Data were collected by conducting observation technique, documentation, and test. It is shown from the results of the study that the ability of children to speak is increasing for every cycle. In the beginning, the cycle reached by only 56% or in the average 51, cycle I reached 60% with mean score 68,08 and cycle 2 reached 97% with the average score 83. From the percentage, it is shown that results of cycle II has passed the minimum score for students in Kindergarten level. In other words, it is proven that singing has been successfully implemented as a strategy in teaching speaking. It has enhanced the ability of children to speak. It is suggested for teachers in Kindergarten level to implement singing as a teaching strategy to bridge the need to teach Kindergarten students to speak during the learning process.